People's Republic of China-Macao Special Administrative Region : 2022 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report, 2022)
Macao SAR's recovery is expected to continue in 2022, but it will take several years before the economy returns to its pre-crisis level. Although strong fiscal support and the financial strength of Macao SAR's casino groups cushioned employment and consumption, the sharp contraction in activity exposed Macao SAR's vulnerability to external forces affecting the inflow of tourists. Short-term risks to the outlook include a re-intensification of the COVID-19 pandemic and an increase in Macao SAR's financial sector stress. The heavy impact of the pandemic on Macao SAR's growth highlights the need to diversify the economy beyond the gaming industry. The high exposure to climate-related shocks poses long-term concerns.